Riesz Potential and Fractional Maximal Function - Ghimire, Santosh (Journal of Advanced College of Engineering and Management, 2021)
In this article, we begin with Riesz potential. We then discuss some properties of the Riesz potential. Finally we discuss a relation of Riesz Potential with fractional maximal function in the sense that fractional maximal function can be controlled by Riesz potential and the fractional maximal function maps the space Lp to Lq whenever the Riesz potential does.